Kunci Kesuksesan Belajar: Motivasi, Disiplin, Kemandirian dan Interaksi dengan Teman Sebaya - Gina Aulia Nurizqi; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
By carrying out this analysis the aim is to determine the influence of learning motivation, Learning Discipline, Learning Independence and Peer Interaction on Learning Readiness. The type of research used is a quantitative method with descriptive analysis. Technique Data collection was carried out online with a questionnaire using a one Likert scale up to five and obtained using a simple random sampling method on 110 respondents with Criteria are active students aged 18-22. Data analysis techniques used in. This research is: Outer Model with Convergent Reliability and Discriminant calculations Validity, Composite Reliability, Cronbach's Alpha and Inner Model with T calculations statistics, R Square, f-Square, and VIF using the SmartPLS 4 (Partial Least Square).